2016
DOI: 10.11621/pir.2016.0107
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation or integration: Similarities and differences between acculturation attitudes of migrants from Central Asia and Russians in Central Russia

Abstract: When acculturation strategies of migrants and acculturation expectations of a host society do not coincide, psychological outcomes for members of the groups in contact can differ significantly. Berry (2013) proposed that intercultural relations can be understood on the basis of three hypotheses: the multiculturalism hypothesis, the integration hypothesis, and the contact hypothesis. Our goal was to test these three hypotheses in Russian majority and Asian minority groups. Migrants from Central Asia (N = 168; 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Researchers studying the applicability of this model for the Russian context report that the main conditions for positive cross-cultural relations in Russia are associated with the support of tolerance, perceived security [15], and acceptance of multiculturalism at the level of interpersonal relations [16] and at the level of public policy [17]. Lebedeva, Tatarko and Berry [18] point to the need to: (1) promote multiculturalism and integration policies;…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Researchers studying the applicability of this model for the Russian context report that the main conditions for positive cross-cultural relations in Russia are associated with the support of tolerance, perceived security [15], and acceptance of multiculturalism at the level of interpersonal relations [16] and at the level of public policy [17]. Lebedeva, Tatarko and Berry [18] point to the need to: (1) promote multiculturalism and integration policies;…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Studies have shown that although cultural diversity is commonly viewed as beneficial by majority Russians, they also support the idea of limiting the rights of non-indigenous people (migrants), as well as the idea that the number of immigrants should be reduced (Mezhnatsional'nye otnosheniya: monitoring FOM, 2014). Several studies provide evidence that in the Russian context, support for multiculturalism is stronger when questions are asked about indigenous minority groups compared to migrant groups (galyapina & lebedeva, 2016;lebedeva & Tatarko, 2013;Ryabichenko & lebedeva, 2016).…”
Section: Identity Management Strategies and Adoption Of Multiculturalmentioning
confidence: 99%
“…Способствует ли выполнение этих трех условий взаимной адаптации представителей различных этнокультурных групп -проблема, которая изучается в разных странах (Dandy, Pe-Pua, 2010;Gui et al, 2016;Hui et al, 2015), включая Россию (Galyapina, Lebedeva, 2016;Lebedeva et al, 2016;Ryabichenko, Lebedeva, 2016). Все эти исследования выполнены в рамках проекта MIRIPS 1 , в котором мультикультурализм понимается как идеология, подразумевающая, что культурное разнообразие -это благо для общества в целом и для его отдельных членов.…”
Section: понятие мультикультурализма и его изучениеunclassified